Ineficacia del procedimiento previsto en el artículo 400 del código orgánico general de procesos, para el remate - Rivadeneyra Grefa, Félix Fredy (2017)
The present research paper whose subject is "INEFFECTIVENESS OF THE PROCEDURE PROVIDED FOR IN ARTICLE 400 OF THE GENERAL ORGANIC CODE OF THE PROCESSES FOR THE REMITTANCE" It is oriented or propose a reform to our legal body with the intention of establishing the auction of a good in a Percentage less than one hundred percent of the amount established. Through the validation of the General Organic Code of Processes, the procedural framework for processes in non-criminal matters has been transformed into Ecuador, a process that includes from the orality of processes to the speed of processes. Within these transcendental changes a new procedure for the auctioning is incorporated into this normative body, this in Art 400, which specifies "Posture requirements. Positions presented for first and second signaling, can not be less than 100 % of the valuation carried out. Which, unlike the previous Law once the expert assessment has been made, the bidders will only be able to carry out their positions based on 100% or more of the real valuation of the asset to be auctioned, not only in the first indication, Postures in this, after the first signaling failed by skirt of offers, in a second sign must be performed the same procedure and under the same rules, that is with positions equal to or greater than 100% of the valuation of the good. In addition, the procedure to be followed is not indicated if the second signaling also does not reach the auction of the good, so the rule is more than being wrong, it is insufficient. From all points of view the rule is inefficient, because under these rules in practice in many cases the auction will not occur and what is even more serious to failure the institution of the auction that aims to enforce the obligation unfulfilled, would be violating the rights of creditors. In our Constitution of the Republic in number 23, Art. 66, recognizes and guarantees to the people the right to property, in all its forms, with social and environmental responsibility and responsibility. We must take into account the Magna Carta that in its Arts. 75 and 82 tells us about the rights to effective protection and legal certainty. I also believe that this legal provision should establish a starting point from which the expert must make the expert valuation of the property, in order not to harm the debtor and the creditor of the property. In this sense, within the executive judgment and with the purpose of securing the obligation contracted by the debtor, the judge, at the request of a party, may order the attachment, which is done immediately to the appraisal and then to the auction of the property.